(untitled) (International Seven Journal of Multidisciplinary, 2024)
Recognizing that there is a lack of knowledge of entrepreneurs about marketing and its importance for organizations, resulting in market gaps. This study aims to present a proposal for a marketing plan in a digital store of men’s clothing and accessories. Thus, for the development of this theme, a theoretical basis was used as a methodology, from renowned marketing authors, among bibliographies and recognized sites in the area. Therefore, it was understood how important it is to be up to date with the changes that the market provides us. The study brings strategies, such as the types of marketing, their theories, tools and concepts, this also includes the SWOT analysis and the 4P’s, also known as the marketing compound. To direct the future entrepreneur, the study helps to find and define your competitions, target audience and their needs and desires, identify problems, know the communication channels, about the concept of entrepreneurship, its importance and its aspects, ending with a case study demonstrating a planning with the expectation of one year, relating the budgets, schedules and based on the proposal idealized to the company, a control will be made to observe if the goals are being met or if it will be necessary to change strategy. Therefore, it was understood how important it is to be on top of the changes that the market provides us, because by knowing it we can analyze the best ways to achieve the goal of placing the company as a reference in the market.